Hematology, hormones, inflammation, and muscle damage in elite and professional soccer players: a systematic review with implications for exercise - Saidi, K.; Abderrahman, A. B.; Hackney, A. C.; Bideau, B.; Zouita, S.; Granacher, U.; Zouhal, H. (Sports Medicine, 2021)
Background: Knowledge of the long-term effects of soccer training on hematological, hormonal, inflammatory, and muscle damage markers and physical performance may help to better design strength and conditioning programs for performance development and injury prevention for the individual player and the team.